ChemInform Abstract: Color‐Tunable Emission and Energy Transfer in Ca3Gd7(PO4) (SiO4)5O2: Ce3+/Tb3+/Mn2+ Phosphors. Issue 7 (22nd February 2013) - Zhang, Yang; Li, Guogang; Geng, Dongling; Shang, Mengmeng; Peng, Chong; Lin, Jun
Abstract The color‐tunable title phosphors are prepared by solid state reaction of stoichiometric mixtures of CaCO3, Gd2O3, (NH4)2HPO4, SiO2, CeO2, Tb4O7, and MnCO3 (10%H2/90%N2, 1400 °C, 3 h).